Clinical characteristic of myelin oligodendrocyte glycoprotein antibody associated cortical encephalitis in adults and outcomes following glucocorticoid therapy - Wu, Yuqing; Zhou, Hao; Ci, Xiaojiao; Lin, Liuyu; Zhang, Da; Lu, Jie (Frontiers in Aging Neuroscience, 2023)
Objective: To describe the clinical and radiological features, as well as outcomes following glucocorticoid therapy and recurrence in adults suffering from cortical encephalitis associated with myelin oligodendrocyte glycoprotein (MOG) antibody. Methods: The clinical information of nine adult patients suffering from cortical encephalitis associated with MOG antibody admitted to the Affiliated Brain Hospital of Nanjing Medical University from 2020 to 2022 was systematically reviewed. The clinical symptoms, laboratory data, imaging results, outcomes following glucocorticoid therapy and recurrence were evaluated. Result: A total of 9 patients positive for MOG antibody and suffering from cortical encephalitis were included in our study (55.6% men, median age 29 years, 15-57 years). The most common clinical symptoms included headache, fever , and generalized seizures. The main features of cerebrospinal fluid examination were increased intracranial pressure, pleocytosis, and elevated CSF protein. All patients were subjected to MRI and the images of eight of them showed T2 and/flair image hyperintense lesions. All patients received glucocorticoid therapy in the acute phase and in remission, and eight of them received an intravenous high dose of methylprednisolone. One patient was treated with low-dose prednisolone tablets. Seven (77.8%) patients were wholly recovered at discharge, and 2 (22.2%) patients were left with slight symptoms. During the median 9-month follow-up (range: 2-36 months), 2 (22.2%) patients developed recurrence. Conclusion: The clinical manifestations of adult MOG antibody-associated cortical encephalitis were significantly different from those of the typical MOG antibody-associated disease (MOGAD). Patients in the acute phase of the disease were prone to show signs similar to central nervous system infection. In addition, seizures were common in MOG antibody-related encephalitis. Brain MRI results showed that the distribution of cerebral cortex lesions was closely related to the classification of cortical encephalitis. Based on the patient's response to the treatment, glucocorticoid therapy was effective against MOG antibody-associated cortical encephalitis, which is consistent with the treatment response and clinical prognosis of MOGAD. Therefore, our opinion was that MOG antibody might be the "responsible antibody" in MOG antibody-associated cortical encephalitis, although further studies are needed to confirm this hypothesis.